Basic order and marked orders in South Peruvian Quechua - Sánchez Arroba, María Elena (2007)
This paper proposes a description of the pragmatic and formal factors that correlate with sequences that deviate from the basic order of constituents in Quechua. The SOV structure is assumed as the basic order of this language, and the OVS sequence is linked to subject focus and direct style; to OSV, to object topicalization; to VSO and VOS, to a counter-expectation orational focus and to focused or heavy arguments; and finally, to SVO, to object focus and the establishment of conclusions. The proposal is based on a functional linguistic analysis5 of several narrative texts in Quechua variants from southern Peru.